The Correlation Of Mid-Upper Arm Circumference With Birth Weight Based In Puskesmas Kecamatan Cipondoh Tangerang January-December 2013 - Dwi Mursita Sari; Sugeng Wiyono (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
Birth weight is a predictor for the infant's ability to survive, grow, and evolve, even as a predictor of health status in the next life cycle. In 2012, in the city of Tangerang number of low birth weight increased from 436 cases to 647 cases. This research was conducted in Puskesmas Kecamatan Cipondoh on January 24, June 20 and 23 June 2014. The design of this research used a retrospective design with a sample of 140 people. Average birth weight 2867.14 ± 373.674 gram, the size of the mother MUAC 25.46 ± 3.333 cm, weight gain during pregnancy of 9.67 ± 3.483 kg, maternal height 153.9 ± 5.894 cm, and maternal age 28,28 ± 6.226 years. Pregnant mother who have a risk parity of 42 people (30%) and 98 people are not at risk (70%), pregnant women who have completed primary school education 20 (14.3%), graduated SMP/MTS 42 people (30%), graduated SMA/MA 70 people (50%), and graduated from PT 8 people (5.7%), pregnant women who worked 20 persons (14.3%) and didn’t work 120 people (85.7%). Based on statistical tests, there is a relationship between birth weight based MUAC mother, mother body weight gain, and maternal height. However, there was no relationship with maternal age and there was no difference in birth weight by maternal parity. Pregnant women should consume nutritious foods in accordance with their needs well before and during pregnancy.